2013
DOI: 10.1073/pnas.1219076110
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic link between β barrel assembly and the initiation of autotransporter secretion

Abstract: Autotransporters are bacterial virulence factors that contain an N-terminal extracellular ("passenger") domain and a C-terminal β barrel ("β") domain that anchors the protein to the outer membrane. The β domain is required for passenger domain secretion, but its exact role in autotransporter biogenesis is unclear. Here we describe insights into the function of the β domain that emerged from an analysis of mutations in the Escherichia coli O157:H7 autotransporter EspP. We found that the G1066A and G1081D mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
128
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(133 citation statements)
references
References 42 publications
(75 reference statements)
5
128
0
Order By: Relevance
“…Conversely, mutational analyses of EspP show delayed passenger domain translocation in the mutant proteins EspPG 1066 A and EspPG 1081 D, that did not affect interactions with the periplasmic chaperone Skp nor the BAM complex 42 . It was concluded that these mutations affect the insertion of the EspP barrel domain into the plane of the outer membrane 42 . Analysis of the crystal structure of EspP shows that these mutations, EspPG 1066 A and EspPG 1081 D, would each affect a mortise-tenon structure (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Conversely, mutational analyses of EspP show delayed passenger domain translocation in the mutant proteins EspPG 1066 A and EspPG 1081 D, that did not affect interactions with the periplasmic chaperone Skp nor the BAM complex 42 . It was concluded that these mutations affect the insertion of the EspP barrel domain into the plane of the outer membrane 42 . Analysis of the crystal structure of EspP shows that these mutations, EspPG 1066 A and EspPG 1081 D, would each affect a mortise-tenon structure (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The Bam complex appears to promote the secretion of the passenger domain as well as the membrane insertion of the β-barrel, and the assembly of EspP into proteoliposomes that contain the Bam complex has been reconstituted in vitro (40). The passenger domain is secreted in a C-to N-terminal direction (57,58), and even large N-terminal deletions do not affect protein biogenesis (31,59). Because we wished to focus on the assembly of the EspP β-barrel, we used a ~35 kD truncated version of EspP that lacks most of the passenger domain (EspP∆5, residues 998-1300) in our experiments.…”
Section: The Bam Complex Catalyzes Efficient Folding Of Espp Into a Wmentioning
confidence: 99%
“…Finally, a component of the Bam complex (BamA) has been shown to interact with the passenger domain during the translocation reaction (7). Although the β-domain does appear to play a role in translocation (20,21), available evidence suggests that the Bam complex promotes the membrane insertion of the β-domain and the secretion of the passenger domain in a concerted reaction (7,8).…”
mentioning
confidence: 99%